Efeitos das alternativas de herbicidas aplicados em nível comercial na cultura da mandioca no balanço de massa final das raízes - Abreu, Magno Luiz [UNESP]; Bicudo, Silvio José [UNESP]; Curcelli, Felipe [UNESP]; Aguiar, Eduardo Barreto [UNESP]; Brachtvogel, Elizeu Luiz [UNESP] (My University, 2010)
This essay aimed to evaluate of the effects of alternative herbicides applied on a commercial level in cassava crop in the mass end of the roots The experiments were conducted in Botucatu / SP, Brazil, in a clay soil and São Manuel / SP, Brazil, in sandy soil, in 2008 croprowing season. The treatments was combinated in a 11 X 2 factorial (11 herbicides and 2 varieties) and disposed in a randomized block design. The treatments the herbicides tested was ametryne (1000g ha-1 ), clomazone (500 g ha-1 ), ametryne + clomazone (750 + 500 g ha-1 ) and atrazine (500 g ha-1 ) applied in pre-emergence of cassava,haloxyfof-methyl (48 g ha-1 ), sethoxydim (200 g ha-1 ), fluazifop-p-butyl (100 g ha-1 ), quizalofop-p-ethyl (75 g ha-1 ), fomezafen (225 g ha-1 ) and bentazon (720 g ha-1 ), applied post-emergence of culture as well as an control untreated end two varieties IAC14 and IAC576-70. For the implementation it was used a backpack sprayer, pressurized CO2 and equipped with bar application with five Teejet XR 110 02vs spaced at 0.50 m, with consumption volume of 200 L ha-1 of water. The material was processed in the laboratory for extraction of starch from CERAT (Centre for Tropical Root Starches UNESP / Botucatu). The starch content was found are the same industries that can extract. The starch content was unaffected in both varieties and environments studied.

O objetivo deste trabalho é avaliar os efeitos das alternativas de herbicidas aplicadas em nível comercial na cultura da mandioca no balanço de massa final das raízes. O experimento foi instalado nos municípios de Botucatu/SP e São Manuel/SP, no ano agrícola de 2008. Os herbicidas utilizados foram: ametrine (1000g ha-1 ), clomazone (500g ha-1 ), ametrine + clomazone (750 + 500g ha-1 ) e Atrazine (500g ha-1 ), aplicados logo após o plantio em pré-emergência da mandioca e haloxyfof-methil (48 g ha-1 ), sethoxydim (200 g ha-1 ), fluazifop-p-butil (100 g ha-1 ), quizalofop-p-ethil (75 g ha-1 ), fomezafem (225 g ha-1 ) e bentazon (720 g ha-1 ), aplicados sob pós emergência, além de uma testemunha sem aplicação e outra mantida com mato. Foi utilizado o delineamento em blocos ao acaso com quatro repetições. Utilizou-se um pulverizador costal, pressurizado a CO2 e equipado com barra de aplicação com cinco pontas Teejet XR 110 02VS, com um consumo de calda de 200 L ha-1 . O material foi processado no laboratório de extração de amidos do CERAT (Centro de Raízes e Amidos Tropicais da UNESP/BOTUCATU). Os teores de amido encontrados são os mesmos que as indústrias conseguem extrair. O teor de amido não foi afetado em ambas as variedades e ambientes estudados.
Effects of alternative level of herbicides applied in trade in culture of cassava on the final mass balance of roots
Keywords: Manihot esculenta; Phytotoxicity; Mass balance; Manihot esculenta; Fitotoxicidade; Balanço de massa